2000
DOI: 10.1002/1097-4636(20000905)51:3<500::aid-jbm26>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan film enriched with an antioxidant agent, taurine, in fenestration defects

Abstract: A natural polysaccharide, chitosan (poly-N-acetyl glucosaminoglycan), which is a nontoxic and bioabsorbable polymer, has been shown to have hemostatic and antibacterial effects. An amino acid, taurine, is considered to be beneficial for regulating the inflammation process. The purpose of this study was to investigate the synergistic effects of taurine and chitosan in the experimental defects at the vestibular bone of maxillary canine teeth in six dogs. Chitosan films were prepared as delivery system with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…However, another biomaterial subcutaneously inducing a similar mixed macrophage and neutrophil response [52,53], chitosan, has been successfully applied in vivo for articular cartilage regeneration [54], suggesting also intra-articular application of the LDH-pNIPAAM gels would be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…However, another biomaterial subcutaneously inducing a similar mixed macrophage and neutrophil response [52,53], chitosan, has been successfully applied in vivo for articular cartilage regeneration [54], suggesting also intra-articular application of the LDH-pNIPAAM gels would be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Важ-ная причина их возникновения и развития -сбой в си-стеме регуляции окислительно-восстановительных пре-вращений и в первую очередь нарушение соотношения анти-, прооксидантных и детоксикантных систем. При этом начальные этапы запуска свободнорадикальных окислительных процессов при разных патологических со-стояниях могут различаться, но в последующем их на-правленность и интенсивность теряют специфичность и зависят от состояния и степени мобилизации антиокси-дантной и детоксикантной защиты [7,8,22,39,41].…”
Section: стоматология 2 2015unclassified
“…Так, весьма пер-спективны металлокомплексы ряда жизненно важных элементов на основе азольных лигандов, которые прини-мают активное участие в разнообразных ферментативных процессах и связывании микроэлементов в живых орга-низмах. Эти «координационные» соединения, обладая широким спектром направленного действия, способству-ют стабилизации гомеостаза, малотоксичны, легкодози-руемы и, что самое важное -высокоэффективны [3,7,8,31,39].…”
Section: стоматология 2 2015unclassified
“…15 Metronidazole-loaded chitosan microparticles were successfully prepared by an emulsion cross-linking method and might be suitable for future periodontitis treatment. 16 A clinical study reported that chitosan gel incorporated with or without 15% metronidazole was effective in probing depth reduction in patients with chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%